NILAI, PERAN, SERTA FUNGSI SHALAT DAN MASJID DALAM MENYIKAPI PROBLEMATIKA MASYARAKAT MODERN - Taufik Kurahman (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2018)
Religion doesn’t only teach vertical worship, but also teaches horizontal worship. The point is that religion leads people, as social beings, to live kindly with others. Shalat in Islam contains two aspects above. Prayers (shalat) are preferred for doing congregrated. The aims are to gether people in one place, so they able to socialize with others. In addition, masjid can also be used as a socialization place, not only as a worship place. Even less in modern era, where there is a distance between individuals and their society. To treat the disease of modern society, the author sees that masjid can be used as a medium to unite the individualist modern society. In this case, the autor makes Masjid Nabawi as a model role. By observing the values of congregational prayer, roles and functions of Masjid Nabawi in Prophet era, the author offers that masjid can be used as a place for society to socialize.